Additional trackways found in the Dinosaur Park Formation subsequent to Skyline Tracksite discovery. - Phil R. Bell (7238132) (2025)
A–C) ‘Cathedral Tracksite’ after initial discovery with minimal excavation (A) Sept 9, 2024, and following moderate excavation, Sept 12, 2024 (B), with track interpretation (C) showing a probable ceratopsian track (ce) and a large theropod track (t). Black arrows in A, B indicate the same sediment displacement rim for reference. D) Unexcavated isolated tridactyl print (‘Mueller Tracksite’ Aug 11, 2024, photo credit Andre Mueller). E) Unexcavated potential trackway (‘Lambert Tracksite’, Oct 25, 2024, photo credit Dawson Lambert).